ANALISIS LITERASI PEMBELAJARAN SISWA SEKOLAH DASAR DALAM MEMBANGUN PEMAHAMAN MEMBACA DI MIS ASY-SYA’BAN KARANGSARI - Rizki Latifatun Nisa; Bagas Mukti Nasrowi (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the condition of learning literacy among elementary school students in developing reading comprehension at MIS Asy-Sya’ban Karangsari. This research employed a qualitative method with a case study approach to gain an in-depth understanding of students’ learning literacy conditions based on actual classroom practices. The data sources were teachers and students of MIS Asy-Sya’ban Karangsari. Data were collected through semi-structured interviews and non-participant observation, while data validity was tested using source triangulation, method triangulation, and time triangulation. Data analysis referred to the Miles and Huberman model, which consists of data condensation, data display, and data verification. The findings revealed that students’ learning literacy had not been optimally developed, particularly in reading and understanding learning materials. Students tended to become bored easily when reading long texts and showed greater interest in learning activities that involved visual, interactive, and digital media. The use of learning media such as instructional videos, PowerPoint, flipbook, and smartphones in learning activities was able to increase students’ attention, participation, and understanding of the material. However, low reading interest, the habit of obtaining instant information, and limited learning facilities remained obstacles in supporting students’ reading comprehension skills. Therefore, appropriate learning strategies are needed to integrate literacy activities with engaging learning media that suit the characteristics of elementary school students.